Exploring EFL Students' Creativity and Engagement with AI Chatbot in Web-Based English Course - Mushaddiq Mushaddiq; Nurdin Noni; Abdullah Abdullah; Muhammad Tahir (PT. Global Research Collaboration, 2024)
This research explores the role of AI-based chatbot tools in promoting creativity and engagement among English as a Foreign Language (EFL) students in web-based English material development course. A qualitative research design was employed, involving in-depth interviews and observation checklists. The research was conducted at the English Education Faculty in Parangtambung of Universitas Negeri Makassar, with data collection spanning from May 12, 2024, to June 9, 2024. Participants included five undergraduate students from the 6th semester based on their familiarity with AI chatbots. The subjects of this research were undergraduate students enrolled in the English web-based material development course. Specifically, five students with prior experience or familiarity with AI chatbots were chosen to provide detailed insights through interviews and observations. The findings indicate that AI chatbots significantly encourage creativity among EFL students by providing a safe space for language experimentation and immediate feedback. Students reported increased engagement and enjoyment in their learning process. The research concludes that while AI chatbots can effectively foster creativity and engagement, careful integration and continuous monitoring are necessary to maximize their educational benefits.